Prevalence and correlates of suicidal ideation among older adults attending primary care clinics in Wuhan, China: A multicenter cross-sectional study - Zhu, Xiao-Min; Xu, Yan-Min; Wang, Zong-Qin; Zhong, Bao-Liang (Frontiers in Psychiatry, 2022)
Background: Primary care represents an ideal setting for screening for and managing suicidal older adults but the clinical epidemiology of suicidal ideation in Chinese older primary care patients remains unclear. This study investigated the prevalence and correlates of suicidal ideation in Chinese older adults receiving primary care. Methods: This multicenter cross-sectional survey included a total of 769 older adults (≥65 years) from seven urban and six rural primary care clinics in Wuhan, China. The presence of depressive symptoms and suicidal ideation was assessed with the Geriatric Depression Scale and a single-item question “In the past twelve months, did you think about ending your life?”, respectively. Results: The twelve-month prevalence of suicidal ideation in older primary care patients was 16.6%. Significant correlates of suicidal ideation were poor economic status (vs. good, OR=2.80, P=0.008), heart disease (OR=2.48, P=0.005), chronic gastric ulcer (OR=3.55, P=0.012), arthritis (OR=2.10, P=0.042), and depressive symptoms (OR=11.29, P<0.001). Conclusions: Suicidal ideation is common among older adults attending Chinese primary care clinics. It is necessary to integrate psychological crisis intervention into primary care to prevent late-life suicide.